The Promise of Confidentiality: New Lights for Scientific Research and Professional Practice in Mental Health [a Promessa de Confidencialidade: Novas Luzes Para a Investigação Científica E Prática Profissional Em Saúde Mental] [la Promesa de Confidencialidad: Nuevas Luces Para la Investigación Científica y la Práctica Profesional en Salud Mental] - Pasmanik-Volochinsky, D; Winkler-Muller, M (Organizacion Panamericana de la Salud, 2018)
In this paper the concept of confidentiality is revisited in the light of the challenges arising from technological and communications advances and their applications in clinical practice and scientific research. The analysis is based on the presentation of philosophical background as well as the distinction and precision regarding related concepts: intimacy, privacy, anonymity, and professional secret. A counterpoint between privacy rights of patients and participants of scientific research and professional secrecy and confidentiality as professional duty is done. Also new challenges to privacy are developed in professional practice and scientific research in mental health, like the protection of confidentiality of the electronic clinical file. The authors conclude emphasizing the need to include the subject in the ethical and legal reflection in research and professional education. © 2018, Organizacion Panamericana de la Salud. All rights reserved.